KORELASI VARIASI MENGAJAR GURU PAK DENGAN HASIL BELAJAR PAK SISWA KELAS XI - lidya situmeang (IAKN Tarutung, 2019)
vAbstract, The purpose of this study was to find out the Correlation of Teaching Variation of PAKTeacher and Learning Outcomes of PAK student of XI Class of. The hypothesis that there is asignificant correlation between the Teachers' Variation in PAK Teachers and the LearningOutcomes of Class XI, with a sample of 46 people. The data collected by a closed questionnaire,with of questions as many as 25 items which are arranged based on indicators according and havebeen tested for validity and reliability tests, for the Y the is taken from student grades. The resultsof data analysis showed that there was a significant correlation between the PAK TeacherTeaching Variation and the Learning Outcomes of Class XI, this was proven by r count r table of0.697 0.291 and t count t table of 6.447 2,021 and the magnitude of the relationship is 48,58%Keyword : Variation in Teaching, Learning Outcomes